2000
DOI: 10.1093/humrep/15.5.1112
|View full text |Cite
|
Sign up to set email alerts
|

The use of two density gradient centrifugation techniques and the swim-up method to separate spermatozoa with chromatin and nuclear DNA anomalies

Abstract: Human semen is heterogeneous in quality, not only between males but also within a single ejaculate. Differences in quality are evident, both when examining the classical parameters of sperm number, motility and morphology and in the integrity of the sperm nucleus. The aim of this study was to determine the efficiency of the PureSperm((R)), Percoll((R)) and swim-up preparation techniques to eliminate spermatozoa with nuclear anomalies. Semen samples were collected, washed and one part of the semen spread on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
120
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(140 citation statements)
references
References 23 publications
15
120
2
3
Order By: Relevance
“…While one study showed that the DGC is more effective than SUP in reducing the percentage of sperm with DNA damage [25], another one, in contrast, demonstrated that SUP recovers lower percentage of sperm with fragmented DNA as compared to DGC [37]. Enciso et al [11] showed that SUP and DGC are equally efficient in eliminating spermatozoa containing double-strand DNA damage and sperm with highly damaged DNA, as characterized by the presence of both single-and double-strand DNA breaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While one study showed that the DGC is more effective than SUP in reducing the percentage of sperm with DNA damage [25], another one, in contrast, demonstrated that SUP recovers lower percentage of sperm with fragmented DNA as compared to DGC [37]. Enciso et al [11] showed that SUP and DGC are equally efficient in eliminating spermatozoa containing double-strand DNA damage and sperm with highly damaged DNA, as characterized by the presence of both single-and double-strand DNA breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies addressed whether there was any differences between these two methods regarding sperm motility and concentration after semen preparation and the outcomes of intrauterine insemination [1,6,10,25,35], in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) [9,[18][19][20]22,32,33] However the results are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have compared the effects of DGC and swim-up or both on sperm DNA integrity, the findings have been discordant [20,24]. Chiamchanya et al [25] compared the sperm quality Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications 25,26 have shown that density gradient centrifugation increases the isolation of spermatozoa with normal morphology and DNA integrity. However, our study demonstrated that the incidence of sperm aneuploidy and DNA fragmentation was still high in males with a sperm concentration of ,5310 6 million ml 21 after the process of density gradient preparation.…”
Section: Discussionmentioning
confidence: 95%